Stability of Antibiotics and Chemotherapeutics in Agar Plates - Ryan, Kenneth J. (1970)
The stability of chemotherapeutic agents incorporated into agar plates was studied by comparison of minimum inhibitory concentrations on fresh and stored plates and by direct bioassay of the chemotherapeutic agar plates. Plates were stored in sealed bags at 4 C. No loss of bioactivity was demonstrated after 30 days of storage in plates containing methicillin, erythromycin, cephalothin, tetracycline, chloramphenicol, kanamycin, streptomycin, polymyxin B, or nalidixic acid. Penicillin G, ampicillin, and nitrofurantoin showed statistically significant losses of activity after 4 weeks. None of the chemotherapeutics tested showed significant loss in activity after 1 week.